2015
DOI: 10.1016/j.memsci.2015.05.047
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of polyethersulfone nanocomposite membranes for the removal of endocrine disrupting micropollutants from wastewater. Mechanisms and performance

Abstract: The addition of carbon nanotubes to improves the removal and adsorption of endocrine disrupting micropollutants (bisphenol A and nonylphenol). Increasing the SWCNT (single walled carbon nanotubes) content increases removal and diminishes reversible and irreversible fouling.The isoelectric point of the SWCNT containing membranes decreases when the content of nanotubes increases with more negative charges at alkaline pH. Because, the nanotube loaded membranes are also less hydrophilic and bisphenol and nonylphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 45 publications
(42 reference statements)
0
25
0
Order By: Relevance
“…In order to improve the effectiveness of polyethersulfone (PES) membranes for mi-cropollutant removal, Kaminska et al [39] inserted "small amounts of single walled carbon nanotubes" in this membrane, which increased the adsorption of bisphenol A and nonylphenol. But, the authors warn about that increase of the pressure can diminish the removal, probably because the porosity of the membrane and the convection through it.…”
Section: Membrane Separation Processmentioning
confidence: 99%
“…In order to improve the effectiveness of polyethersulfone (PES) membranes for mi-cropollutant removal, Kaminska et al [39] inserted "small amounts of single walled carbon nanotubes" in this membrane, which increased the adsorption of bisphenol A and nonylphenol. But, the authors warn about that increase of the pressure can diminish the removal, probably because the porosity of the membrane and the convection through it.…”
Section: Membrane Separation Processmentioning
confidence: 99%
“…The higher j values of the PES membrane at a higher pH shows that the surfaces of the PES membranes were more negative due to the nature of the sulphonic group (O¼S¼O), which dissociates markedly at high pH values [45]. The observed positive charge on the PES membrane surface could be attributed to positive ion adsorption in the course of measuring the streaming potential [37]. In contrast, j of the N-CNT/PES blend membranes was observed to be more positive at lower pH and more negative at higher pH with IEPs at pH 7.0, 6.8, 6.0, and 5.8 for the 0.01, 0.03, 0.05, and 0.1 wt% N-CNT/PES blend membranes, respectively.…”
Section: Effect Of Ph On J Of Pes Membranes and N-cnt/pes Blend Membrmentioning
confidence: 96%
“…A study by Kaminska et al revealed that the incorporation of small quantities of single‐walled carbon nanotubes (SWCNT) in PES membranes improved adsorption and removal of endocrine disrupting micropollutants (technical 4‐nonylphenol, NP, and bisphenol A, BPA) from synthetic wastewater. Fabrication of nitrogen‐doped carbon nanotubes/polyethersulfone (N‐CNT/PES) blend membranes provides a unique opportunity to eliminate these recalcitrant compounds, that is, EMPs, from drinking water systems .…”
Section: Introductionmentioning
confidence: 99%
“…Several techniques, including advanced oxidation processes (AOPs) [9][10][11], membrane filtration [12,13], coagulation [14], and adsorption [15,16] have been used to remove micropollutants from different aqueous media. AOPs and membrane filtration are very effective for the elimination of…”
Section: Introductionmentioning
confidence: 99%